2020
DOI: 10.3324/haematol.2019.245092
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency-induced thrombocytosis increases thrombotic tendency in rats

Abstract: Iron deficiency (ID) is globally prevalent, and apart from anemia is associated with thrombocytosis. While considered benign, studies linking thrombotic events with prior ID anemia suggest otherwise. Herein we used animal models to assess the influence of ID on thrombotic tendency. Sprague-Dawley rats were fed control or iron deficient diets and ferric carboxymaltose was used to reverse ID. Thrombosis was induced via stenosis of the inferior vena cava or damage to the right carotid artery using ferric chloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In addition, platelet adhesion and aggregation were impaired. Taking into account data obtained in this model, the authors concluded that anemia of inflammation, caused by HAMP-mediated iron sequestration in the liver, spleen and macrophages, as possibly occurs in COVID-19 patients, may be considered a functional iron deficiency (ID) and patients affected by this condition should be treated as patients with high risk of thrombosis [139].…”
Section: Cq/hcq Treatment Decreasing Cytokine and Hamp Release May mentioning
confidence: 99%
“…In addition, platelet adhesion and aggregation were impaired. Taking into account data obtained in this model, the authors concluded that anemia of inflammation, caused by HAMP-mediated iron sequestration in the liver, spleen and macrophages, as possibly occurs in COVID-19 patients, may be considered a functional iron deficiency (ID) and patients affected by this condition should be treated as patients with high risk of thrombosis [139].…”
Section: Cq/hcq Treatment Decreasing Cytokine and Hamp Release May mentioning
confidence: 99%
“…Iron deficiency anemia itself has been shown to be associated with thrombotic events in several small retrospective studies 13‐16 . Although recent animal studies demonstrated an elevated thrombotic risk in iron deficient mice with thrombus size correlating with platelet count 17 , whether the elevated thrombotic risk in IDA can be attributed to thrombocytosis has not been clearly elucidated in human analyses. There are numerous case reports describing thrombotic events (particularly in unusual sites) in patients with thrombocytosis reactive to IDA and no other thrombotic risks suggesting a possible relationship 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Haematologica, Jimenez and colleagues describe an animal model of iron deficiency, using Sprague-Dawley rats, which could offer unique opportunities to explore multiple pathophysiological mechanisms for thrombocytosis and venous thrombogenesis. 5 Furthermore, using sensitive histological and sophisticated high-frequency ultrasound techniques, the investigators were able to track the development and progression of thrombus formation. They were then able to correlate those changes with the generation of ex vivo biomarkers of platelet activation and indicators of global hemostasis.…”
mentioning
confidence: 99%